2020
DOI: 10.21273/hortsci15036-20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drought Tolerance in Arkansas Cowpea Lines at Seedling Stage

Abstract: Cowpea [Vigna unguiculate (L.) Walp.] is not only a healthy, nutritious, and versatile leguminous crop; it also has a relatively high adaptation to drought. Research has shown that cowpea lines have a high tolerance to drought, and many of them can survive more than 40 days under scorching and dry conditions. The cowpea (Southern pea) breeding program at the University of Arkansas has been active for more than 50 years and has produced more than 1000 advanced breeding lines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…In this study, we observed that drought stress caused progressive declines in the growth rate of cowpea genotypes to slow down as the stress becomes intense with signi cant variation among the genotypes, as evident in the reduction in plant height and number of trifoliates. A similar decline in the growth rate of cowpea under drought stress at seedling was also observed in 36 cowpea breeding lines evaluated at the breeding program at the University of Arkansas (Cui et al, 2020), suggesting that growth performance could be reliably used to discriminate the seedling drought stress responses in cowpea. Reduction in trifoliate under stress have been proposed to be a stress coping strategy by cowpea (Cui et al, 2020;Ravelombola et al, 2020).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In this study, we observed that drought stress caused progressive declines in the growth rate of cowpea genotypes to slow down as the stress becomes intense with signi cant variation among the genotypes, as evident in the reduction in plant height and number of trifoliates. A similar decline in the growth rate of cowpea under drought stress at seedling was also observed in 36 cowpea breeding lines evaluated at the breeding program at the University of Arkansas (Cui et al, 2020), suggesting that growth performance could be reliably used to discriminate the seedling drought stress responses in cowpea. Reduction in trifoliate under stress have been proposed to be a stress coping strategy by cowpea (Cui et al, 2020;Ravelombola et al, 2020).…”
Section: Discussionsupporting
confidence: 58%
“…A similar decline in the growth rate of cowpea under drought stress at seedling was also observed in 36 cowpea breeding lines evaluated at the breeding program at the University of Arkansas (Cui et al, 2020), suggesting that growth performance could be reliably used to discriminate the seedling drought stress responses in cowpea. Reduction in trifoliate under stress have been proposed to be a stress coping strategy by cowpea (Cui et al, 2020;Ravelombola et al, 2020). As exempli ed in this research, few drought-tolerant plants stopped growing, and shed their leaves to conserved moisture by reducing surface area for transpiration to survive the period of drought.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Numerous studies have been done and are also on-going due to the enormity of drought stress challenges on cowpea productivity enhancement. In a study by Cui et al (2020), they evaluated cowpea drought tolerance potentials at seedling stage. The experiment was done using a total of 36 cowpeabreeding lines in a completely randomized manner under drought stress conditions.…”
Section: Droughtmentioning
confidence: 99%
“…Only in some erect varieties produced for grain could lodging become an issue (Cui et al, 2020;Sindhu et al, 2019). The path analysis also showed that chlorophyll content estimated by a SPAD meter had positive direct effect on plant AGB when measured in the field (Figure 5).…”
Section: Discussionmentioning
confidence: 88%